Content Representation (CoRe) Calon Guru Biologi pada Konsep Genetika - Elvianasti, Mega (Universitas Muhammadiyah Prof. Dr. Hamka, 2019)
Content Representation (CoRe) is a method used to access the understanding of pre-service teachers about a content or material. CoRe contains a description of concepts or material that are important in teaching a particular topic. This type of research is descriptive research that aims to describe what it is, not modified or treated. The subject of this study was the 6th semester biology teacher candidate students at the Indonesian Education University who were selected using Purposive Sampling techniques. Data in the form of CoRe (Content Representation) compilation documents are analyzed in each major idea in the concept of genetics. In general, biology teacher candidates who are in the upper group research subjects, tend to have big ideas. This can be seen from how the pre-service teacher outlines the answers to each question posed in CoRe, compared to biology teacher candidates who are in the subject of the moderate and low group research.